2012
DOI: 10.1016/j.visres.2012.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Screening and sampling in studies of binocular vision

Abstract: Binocular deficits are relatively common within a typical sample of observers. This has implications for research on binocular vision, as a variety of stereo deficits can affect performance. Despite this, there is no agreed standard for testing stereo capabilities in observers and many studies do not report visual abilities at all. Within the stereo literature, failure to report screening and sampling has the potential to undermine the results of otherwise strictly controlled research. We reviewed research art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 43 publications
0
24
0
1
Order By: Relevance
“…14,15 Some of these are listed in Table 1 along with some of their properties. At its most basic, a stereotest can aim simply to determine whether a patient has any stereo vision at all, without quantifying their stereoacuity.…”
Section: How To Measure Stereo Visionmentioning
confidence: 99%
“…14,15 Some of these are listed in Table 1 along with some of their properties. At its most basic, a stereotest can aim simply to determine whether a patient has any stereo vision at all, without quantifying their stereoacuity.…”
Section: How To Measure Stereo Visionmentioning
confidence: 99%
“…Many studies have reported the abnormal functions of the binocular vision due to ametropia, anisometropia, horizontal-vertical phoria, fixation disparity and age related ocular dysfunctions. [1][2][3][4][5][6][7][8][9][10] These factors affect stereo acuity and differences in stereo acuity exist acuity among the people who are not stereo-blind.…”
Section: Introductionmentioning
confidence: 99%
“…Well-known tests are paper-and-pencil tests like the TNO test and the Titmus test (for a description and comparison, see [1], [2] or [3]). These tests make use of anaglyph or polarized glasses to send different images to both eyes.…”
Section: Introductionmentioning
confidence: 99%
“…These tests make use of anaglyph or polarized glasses to send different images to both eyes. While these tests were thoroughly compared on validity and reliability in several studies [4] [3] and it is shown they are of great value in clinical practice, they are expensive and require trained people. Therefore, our objectives were three-fold.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation